Relationship between Kindergarten Teachers'Emotional Labor and Occupational Well-being: Mediating Effect of Organizational Climate - SUN Yajuan; LIANG Hua; LI Xiufang (Jiaoshi jiaoyu xuebao)
Teachers'occupational well-being is an important indicator of the quality of their educational life and the psychological state. To investigate the relationship between emotional labor and occupational well-being of kindergarten teachers and the effect of organizational climate in both, the Emotional Labor Scale, Occupational Well-Being Scale, and Organizational Climate Scale were used to conduct a survey on kindergarten teachers, and a total of 512 valid questionnaires were collected. The results are as follows.First, surface play strategies negatively impacted on the organizational climate and occupationalwell-being. Second, deep play strategies and natural strategies positively predicted kindergarten organizational climate and preschool teachers'well-being. Third, organizational climate partially mediated the relationship between kindergarten teachers' emotional labor dimensions and occupational well-being. To enhance the occupational well-being of kindergarten teachers, we should insist on both internal training and external shaping to improve the emotional literacy of kindergarten teachers; create a "teacher-friendly" organizational climate with both support and care; and with reduced burden and empowerment, build a multi-party collaboration mechanism to create an inexhaustible source of occupational well-being and lasting power for the development of kindergarten teachers.